Total synthesis of Crotogossamide using an on-resin concomitant cyclization/cleavage reaction. (August 2018) - Bérubé, Christopher; Borgia, Alexandre; Simon, Gaëlle; Grenier, Daniel; Voyer, Normand
Graphical abstract: Highlights: Expedient Crotogossamide synthesis by on-resin concomitant cyclization/cleavage. Antibacterial and anti-biofilm activity of Crotogossamide were investigated. Efficient synthetic strategy towards cyclic peptide phytochemicals using oxime resin. Abstract: Crotogossamide, a cyclic peptide isolated from the latex of Croton gossypifolius, has been synthesized by a rapid and efficient Boc solid-phase peptide synthesis. The strategy takes advantage of the oxime resin nucleophile susceptibility and comprises the synthesis of a linear precursor followed by on-resin head-to-tail concomitant cyclization/cleavage. In addition, we report the first antimicrobial and antibiofilm investigations on Crotogossamide.